Laminate and packaging bag

By incorporating a first adhesive layer with a high elastic modulus and a specific laminate structure, the tearability and openability of polypropylene-based laminates are enhanced, addressing the limitations of existing laminates in packaging applications.

JP2025070924APending Publication Date: 2025-05-02DAI NIPPON PRINTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024017344
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-02-07
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Laminates made with stretched substrates containing polypropylene as the main component and a sealant layer with polypropylene as the main component exhibit poor tearability and openability, making them unsuitable for packaging applications.

Method used

The laminate structure includes a first substrate, a first adhesive layer with an elastic modulus of 30.0 MPa or more, a second adhesive layer, and a sealant layer, all in a specific order, to enhance tearability and openability.

Benefits of technology

This configuration significantly improves the tearability and openability of the laminate, making it more suitable for packaging applications while maintaining excellent gas barrier properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070924000003
    Figure 2025070924000003
  • Figure 2025070924000004
    Figure 2025070924000004
  • Figure 2025070924000005
    Figure 2025070924000005
Patent Text Reader

Abstract

To improve tearability of a laminate comprising a polypropylene stretched substrate and a sealant layer containing polypropylene as the primary component thereof.SOLUTION: Provided is a laminate comprising, in this order in the thickness direction: a first substrate, a first adhesive agent layer, a second substrate, a second adhesive agent layer, and a sealant layer, wherein the first substrate comprises a polypropylene stretched substrate, the second substrate comprises a polypropylene stretched substrate, the sealant layer includes polypropylene as the primary component thereof, the elastic modulus of the first adhesive agent layer is 30.0 MPa or more, and the thickness of the first adhesive agent layer is 0.5 μm or more and 3.0 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate and a packaging bag. [Background technology]

[0002] Polyester films are excellent in mechanical properties, chemical stability, heat resistance, and transparency, and are inexpensive. Therefore, polyester films have been conventionally used as substrates constituting laminates used to produce packaging bags. Depending on the contents filled in the packaging bag, the packaging bag is required to have gas barrier properties such as oxygen barrier properties. To meet this requirement, an inorganic oxide layer containing alumina or silica is formed on the surface of the polyester film (see, for example, Patent Document 1). In recent years, substrates to replace polyester films have been sought. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-053223 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have considered using a stretched substrate containing polypropylene as a main component as a substrate constituting a laminate, instead of a conventional polyester film. Specifically, from the viewpoint of recyclability, the present inventors have considered using a laminate including the stretched substrate and a sealant layer containing polypropylene as a main component. As a result of the consideration, the present inventors have found that such a laminate may have poor tearability, and a packaging bag produced using the laminate may have poor openability.

[0005] One of the problems to be solved by the present disclosure is to improve the tearability of a laminate including an oriented substrate containing polypropylene as a main component and a sealant layer containing polypropylene as a main component. [Means for solving the problem]

[0006] The laminate of the present disclosure comprises a first substrate, a first adhesive layer, a second substrate, a second adhesive layer, and a sealant layer, in that order in the thickness direction, wherein the first substrate comprises an oriented substrate containing polypropylene as a main component, the second substrate comprises an oriented substrate containing polypropylene as a main component, the sealant layer contains polypropylene as a main component, the elastic modulus measured using an atomic force microscope (AFM) on a cross section of the first adhesive layer is 30.0 MPa or more, and the thickness of the first adhesive layer is 0.5 μm or more and 3.0 μm or less. Effect of the Invention

[0007] According to the present disclosure, it is possible to improve the tearability of a laminate comprising a barrier substrate including an oriented substrate containing polypropylene as a main component and an inorganic oxide layer, and a sealant layer containing polypropylene as a main component. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 4] FIG. 4 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 6] FIG. 6 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 7] FIG. 7 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 8] FIG. 8 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 9] FIG. 9 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 10] FIG. 10 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 11] FIG. 11 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 12] FIG. 12 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 13] FIG. 13 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 14] FIG. 14 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 15] FIG. 15 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 16] FIG. 16 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 17] FIG. 17 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 18] FIG. 18 is a front view showing one embodiment of a packaging bag. [Figure 19] FIG. 19 is a perspective view showing one embodiment of a packaging bag. [Figure 20] FIG. 20 is a schematic front view showing one embodiment of a laminate having a notch formed therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In this specification, when multiple upper limit candidates and multiple lower limit candidates are given for a certain parameter, the numerical range of the parameter may be configured by combining any one of the upper limit candidates and any one of the lower limit candidates. As an example, the description "parameter B is preferably A1 or more, more preferably A2 or more, even more preferably A3 or more, and also preferably A4 or less, more preferably A5 or less, and even more preferably A6 or less." will be explained. In this example, the numerical range of parameter B may be A1 or more and A4 or less, A1 or more and A5 or less, A1 or more and A6 or less, A2 or more and A4 or less, A2 or more and A5 or less, A2 or more and A6 or less, A3 or more and A4 or less, A3 or more and A5 or less, or A3 or more and A6 or less.

[0010] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure can be implemented in many different forms, and is not to be interpreted as being limited to the description of the embodiments exemplified below. In the drawings, the width, thickness, shape, etc. of each layer may be shown diagrammatically in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those already explained with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0011] As used herein, the term "main component" in a layer or substrate refers to a component whose content in the layer or substrate is greater than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0012] In the following description, each of the components (for example, polypropylene, α-olefin, resin material, additive, gas barrier resin, adhesive resin, inorganic oxide) may be used alone or in combination of two or more kinds.

[0013] [Laminate] The laminate of the present disclosure comprises a first substrate, a first adhesive layer, a second substrate, a second adhesive layer, and a sealant layer, in this order in the thickness direction (hereinafter also referred to as "in this order").

[0014] The first substrate comprises a stretched substrate containing polypropylene as a main component. The second substrate comprises a stretched substrate containing polypropylene as a main component. The stretched substrate of the first substrate and the stretched substrate of the second substrate may be the same or different. In the following description, the stretched substrate containing polypropylene as a main component is also referred to as a "polypropylene stretched substrate." The sealant layer contains polypropylene as a main component. At least one selected from the first substrate and the second substrate may be a barrier substrate comprising the stretched substrate and an inorganic oxide layer.

[0015] In one embodiment of the laminate of the present disclosure, the first substrate is an oriented polypropylene substrate, and the second substrate is an oriented polypropylene substrate. That is, the laminate includes a first oriented polypropylene substrate, an optional print layer, a first adhesive layer, a second oriented polypropylene substrate, a second adhesive layer, and a sealant layer, in this order. In this embodiment, the laminate does not include a barrier substrate.

[0016] In one embodiment of the laminate of the present disclosure, the first substrate is a stretched polypropylene substrate, and the second substrate is a barrier substrate. That is, the laminate includes a stretched polypropylene substrate, an optional printing layer, a first adhesive layer, a barrier substrate, a second adhesive layer, and a sealant layer, in this order. In this embodiment, the barrier substrate is preferably arranged so that the inorganic oxide layer faces the first adhesive layer, and the stretched polypropylene substrate faces the second adhesive layer. This arrangement can, for example, further suppress deterioration of the inorganic oxide layer.

[0017] In one embodiment of the laminate of the present disclosure, the first substrate is a barrier substrate and the second substrate is an oriented polypropylene substrate. That is, the laminate includes a barrier substrate, an optional printing layer, a first adhesive layer, an oriented polypropylene substrate, a second adhesive layer, and a sealant layer, in this order. In this embodiment, the barrier substrate is preferably arranged so that the inorganic oxide layer faces the first adhesive layer and the oriented polypropylene substrate faces outward.

[0018] In one embodiment, the laminate of the present disclosure exhibits excellent gas barrier properties (e.g., oxygen barrier properties and water vapor barrier properties, particularly oxygen barrier properties). A packaging bag made using the laminate of the present disclosure can suppress the deterioration of gas barrier properties even after heat treatment such as retort treatment and boiling treatment. From the viewpoint of more appropriately protecting the inorganic oxide layer during heat treatment and stabilizing the gas barrier properties, a laminate in which the first substrate is a stretched polypropylene substrate and the second substrate is a barrier substrate is preferred.

[0019] 1 to 17 are schematic cross-sectional views showing an embodiment of a laminate according to the present disclosure. The laminate 1 shown in FIG. 1 comprises, in this order, an oriented polypropylene substrate 10 as a first substrate, a first adhesive layer 40A, an oriented polypropylene substrate 22 as a second substrate, a second adhesive layer 40B, and a sealant layer 30.

[0020] 2 includes, in this order, a stretched polypropylene substrate 10 as a first substrate, a first adhesive layer 40A, a barrier substrate 20 as a second substrate, a second adhesive layer 40B, and a sealant layer 30. The barrier substrate 20 includes a stretched polypropylene substrate 22 and an inorganic oxide layer 24. In this example, the barrier substrate 20 is disposed such that the stretched polypropylene substrate 22 faces the second adhesive layer 40B, and the inorganic oxide layer 24 faces the first adhesive layer 40A.

[0021] FIG. 3 is similar to FIG. 2, except that the barrier substrate 20 includes a surface coating layer 23 between the oriented polypropylene substrate 22 and the inorganic oxide layer 24 . FIG. 4 is similar to FIG. 2, except that the oriented polypropylene substrate 22 includes a polypropylene layer 21 and a surface resin layer 26. In FIG. FIG. 5 is similar to FIG. 4, except that the stretched polypropylene substrate 22 includes an adhesive resin layer 27 between the polypropylene layer 21 and the surface resin layer 26. In FIG. FIG. 6 is similar to FIG. 2, except that the barrier substrate 20 comprises an oriented polypropylene substrate 22, an inorganic oxide layer 24, and a coating layer 25 in this order. FIG. 7 is the same as FIG. 2, except that the barrier substrate 20 includes an oriented polypropylene substrate 22, a surface coating layer 23, an inorganic oxide layer 24, and a coating layer 25, in this order. FIG. 8 is similar to FIG. 6 except that the stretched polypropylene substrate 22 includes a polypropylene layer 21 and a surface resin layer 26. In FIG. FIG. 9 is similar to FIG. 8, except that the stretched polypropylene substrate 22 includes an adhesive resin layer 27 between the polypropylene layer 21 and the surface resin layer 26. In FIG.

[0022] 10 includes, in this order, a barrier substrate 20 as a first substrate, a first adhesive layer 40A, an oriented polypropylene substrate 10 as a second substrate, a second adhesive layer 40B, and a sealant layer 30. The barrier substrate 20 includes an oriented polypropylene substrate 22 and an inorganic oxide layer 24. In this example, the barrier substrate 20 is disposed such that the oriented polypropylene substrate 22 constitutes the outermost layer of the laminate 1, and the inorganic oxide layer 24 faces the first adhesive layer 40A.

[0023] FIG. 11 is similar to FIG. 10 except that the barrier substrate 20 includes a surface coating layer 23 between a stretched polypropylene substrate 22 and an inorganic oxide layer 24 . FIG. 12 is similar to FIG. 10 except that the stretched polypropylene substrate 22 includes a polypropylene layer 21 and a surface resin layer 26. In FIG. FIG. 13 is similar to FIG. 12, except that the stretched polypropylene substrate 22 includes an adhesive resin layer 27 between the polypropylene layer 21 and the surface resin layer 26. In FIG. FIG. 14 is similar to FIG. 10, except that the barrier substrate 20 comprises an oriented polypropylene substrate 22, an inorganic oxide layer 24, and a coating layer 25 in this order. FIG. 15 is similar to FIG. 10, except that the barrier substrate 20 includes an oriented polypropylene substrate 22, a surface coating layer 23, an inorganic oxide layer 24, and a coating layer 25, in this order. FIG. 16 is similar to FIG. 14 except that the oriented polypropylene substrate 22 includes a polypropylene layer 21 and a surface resin layer 26. In FIG. FIG. 17 is similar to FIG. 16 except that the stretched polypropylene substrate 22 includes an adhesive resin layer 27 between the polypropylene layer 21 and the surface resin layer 26 .

[0024] The content ratio of polypropylene to the total amount of resin material contained in the laminate of the present disclosure is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 88% by mass or more, and particularly preferably 90% by mass or more. A packaging bag made using such a laminate has, for example, excellent recyclability. The upper limit of the content ratio of polypropylene to the total amount of resin material contained in the laminate of the present disclosure is not particularly limited, but may be, for example, 99% by mass, 98% by mass, 97% by mass, 96% by mass, 95% by mass, or 94% by mass.

[0025] <Polypropylene oriented base material> The oriented polypropylene substrate contains polypropylene as a major component. The polypropylene may be any of a homopolymer, a random copolymer, and a block copolymer, and may be a mixture of two or more selected from these. As the polypropylene, biomass-derived polypropylene and / or recycled polypropylene may be used. A propylene homopolymer is a polymer of only propylene. A propylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene. A propylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of at least an α-olefin other than propylene. The polymer block of at least an α-olefin other than propylene may be a polymer block of propylene and an α-olefin other than propylene.

[0026] Examples of the α-olefin include α-olefins having 2 to 20 carbon atoms other than propylene, specifically, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene.

[0027] Among polypropylenes, random copolymers are preferred from the viewpoint of transparency, homopolymers are preferred when emphasis is placed on the rigidity and heat resistance of the packaging bag, and block copolymers are preferred when emphasis is placed on the impact resistance of the packaging bag.

[0028] From the viewpoint of film-forming property and processability, the melt flow rate (MFR) of polypropylene is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and also preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, for example, 0.1 g / 10 min or more and 50 g / 10 min or less. The MFR of polypropylene is measured in accordance with JIS K7210-1:2014, Method A, under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0029] It is an index of the stereoregularity of polypropylene. 13 The mesopentad fraction measured by C-NMR is preferably 90 mol% or more, more preferably 95 mol% or more. Polypropylene having a mesopentad fraction of the above lower limit or more has high crystallinity and a high melting point, and therefore the heat resistance of the stretched polypropylene substrate made of the polypropylene is improved. The upper limit of the mesopentad fraction is 100 mol%, but in practice it is 99.9 mol% or less, and more practically it is 99.5 mol% or less. 13 Details of the conditions for measuring the mesopentad fraction by C-NMR are described in the Examples section.

[0030] In addition, among polypropylenes, propylene random copolymers and propylene block copolymers contain α-olefins and the like as copolymerization components other than propylene. Therefore, propylene random copolymers and propylene block copolymers are considered to have lower stereoregularity than polypropylene homopolymers, which are polymers of propylene alone. However, the mesopentad fraction is an index of stereoregularity that does not take into account the content of copolymerization components other than propylene. Therefore, even if the polypropylene has the same mesopentad fraction, if the content of copolymerization components other than propylene is different, the stereoregularity of the polypropylene is considered to be different. For example, polypropylene with a large content of α-olefins is considered to have low stereoregularity, so that it has low crystallinity and low melting point. On the other hand, polypropylene with a small content of α-olefins is considered to have high stereoregularity, so that it has high crystallinity and melting point, and the heat resistance of a polypropylene stretched substrate using the polypropylene is improved. The content of α-olefin in polypropylene is preferably 3 mol% or less, more preferably 2 mol% or less, and even more preferably 1 mol% or less. Polypropylene with an α-olefin content of the above upper limit or less has high stereoregularity, and the heat resistance of a stretched polypropylene substrate using the polypropylene is improved. The lower limit of the content of α-olefin in polypropylene is 0 mol%. For example, the content of α-olefin in a propylene homopolymer is 0 mol%. The details of the method for measuring the ethylene content in polypropylene will be described in the Examples section.

[0031] The polypropylene content in the polypropylene oriented base material is preferably greater than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0032] The oriented polypropylene substrate may contain a resin material other than polypropylene, such as, for example, a polyolefin other than polypropylene, such as polyethylene, an acrylic resin, a vinyl resin, a cellulose resin, a polyamide, a polyester, or an ionomer resin. The stretched polypropylene substrate may contain additives, such as crosslinkers, antioxidants, antiblocking agents, lubricants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0033] The stretched polypropylene substrate is a polypropylene substrate that has been subjected to a stretching treatment. A laminate including the stretched polypropylene substrate is excellent in, for example, heat resistance, impact resistance, water resistance, and dimensional stability, and is suitable as a packaging material for forming a packaging bag that is to be subjected to, for example, a retort treatment or a boiling treatment. The stretching process may be uniaxial stretching or biaxial stretching. The stretching ratio in the case of stretching in the machine direction (flow direction of the substrate, MD direction) is preferably 2 times or more, more preferably 3 times or more, even more preferably 3.5 times or more, and also preferably 15 times or less, more preferably 8 times or less, and even more preferably 7 times or less. The stretching ratio in the case of stretching in the width direction (direction perpendicular to the MD direction, TD direction) is preferably 4 times or more, more preferably 5 times or more, even more preferably 6 times or more, and also preferably 20 times or less, more preferably 17 times or less, and even more preferably 15 times or less. By setting the stretching ratio at a certain level or more, the strength and heat resistance of the substrate can be improved, and the printability of the substrate can be improved. From the viewpoint of the breaking limit of the substrate, the stretching ratio is preferably a certain level or less. In addition, the stretching ratio in the MD direction is preferably smaller than the stretching ratio in the TD direction. The oriented polypropylene substrate is, for example, a biaxially oriented substrate.

[0034] The oriented polypropylene substrate may be surface-treated. This can improve the adhesion between the oriented polypropylene substrate and other layers, for example. Examples of surface treatment methods include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment; and chemical treatments such as oxidation treatment using chemicals. An easy-adhesion layer may be provided on the surface of the stretched polypropylene substrate.

[0035] The oriented polypropylene substrate may have a single layer structure or a multi-layer structure. The thickness of the stretched polypropylene substrate is preferably 10 μm or more, more preferably 15 μm or more, and also preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less. A laminate having a stretched substrate with a thickness equal to or greater than the lower limit has, for example, excellent strength and heat resistance. A laminate having a stretched substrate with a thickness equal to or less than the upper limit has, for example, excellent processability.

[0036] In this specification, the thickness of the substrate and each layer is measured as follows. A block is prepared by embedding the laminate in an embedding resin, and the block is cut using a commercially available rotary microtome at room temperature (25°C) to prepare a cross section of the laminate. The cross section is obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing is performed with a diamond knife. The thickness of the substrate and each layer is the arithmetic average value of the thicknesses at five points measured by observing the cross section using a scanning electron microscope (SEM, Hitachi, Ltd., SU8000).

[0037] <Barrier substrate> The barrier substrate comprises a stretched polypropylene substrate and an inorganic oxide layer. The barrier substrate comprises, for example, a stretched polypropylene substrate and an inorganic oxide layer provided on one surface of the stretched substrate. The barrier substrate may comprise a surface coating layer between the stretched polypropylene substrate and the inorganic oxide layer. The barrier substrate may comprise a coating layer on the inorganic oxide layer. The barrier substrate may have transparency.

[0038] (Polypropylene oriented base material) The oriented polypropylene substrate in the barrier substrate may be the oriented polypropylene substrate described in the section <oriented polypropylene substrate>. The oriented polypropylene substrate in the first substrate and the oriented polypropylene substrate in the second substrate may be the same or different.

[0039] The stretched polypropylene substrate provided in the barrier substrate may be, for example, a stretched substrate of another embodiment that includes a polypropylene layer, an optional adhesive resin layer, and a surface resin layer described later in this order. In this embodiment, the barrier substrate includes a stretched substrate of another embodiment and an inorganic oxide layer provided on the surface resin layer of the stretched substrate. In this embodiment, the barrier substrate includes a polypropylene layer, an optional adhesive resin layer, a surface resin layer, and an inorganic oxide layer in this order. In one embodiment, the stretched substrate of another embodiment is a coextruded stretched resin film. The coextruded stretched resin film can be produced, for example, by forming a laminated film using a T-die method or an inflation method, and then stretching the laminated film.

[0040] In other embodiments, the stretching treatment of the stretched substrate may be uniaxial stretching or biaxial stretching. The stretching ratio in the MD direction is preferably 2 times or more, more preferably 3 times or more, and even more preferably 3.5 times or more, and is preferably 15 times or less, more preferably 8 times or less, and even more preferably 7 times or less. The stretching ratio in the TD direction is preferably 4 times or more, more preferably 5 times or more, and even more preferably 6 times or more, and is preferably 20 times or less, more preferably 17 times or less, and even more preferably 15 times or less. The stretching ratio in the MD direction is preferably smaller than the stretching ratio in the TD direction.

[0041] (Surface coating layer) The barrier substrate may include a surface coating layer containing a resin material having a polar group between the stretched polypropylene substrate and the inorganic oxide layer. Such a barrier substrate has excellent adhesion to the inorganic oxide layer and also has excellent gas barrier properties. Such a barrier substrate includes, in this order, a stretched polypropylene substrate, a surface coating layer, and an inorganic oxide layer.

[0042] The polar group refers to a group containing one or more heteroatoms, and examples thereof include ester group, epoxy group, hydroxyl group, amino group, amide group, urethane group, carboxyl group, carbonyl group, carboxylic anhydride group, sulfo group, thiol group, and halogen group. Among these, carboxyl group, carbonyl group, ester group, hydroxyl group, amino group, amide group, and urethane group are preferred, and carboxyl group, hydroxyl group, amide group, and urethane group are more preferred.

[0043] Examples of resin materials having a polar group include ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVA), polyester, polyethyleneimine, hydroxyl-containing acrylic resin, polyamides such as nylon 6, nylon 6,6, MXD nylon, and amorphous nylon, and polyurethane. Among these, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, hydroxyl-containing acrylic resin, polyamide, and polyurethane are more preferred.

[0044] The surface coating layer can be formed, for example, using a water-based emulsion or a solvent-based emulsion. Examples of the water-based emulsion include a polyamide-based emulsion, a polyethylene-based emulsion, and a polyurethane-based emulsion. Examples of the solvent-based emulsion include an acrylic resin-based emulsion and a polyester-based emulsion.

[0045] The content of the resin material having a polar group in the surface coat layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. The surface coating layer may contain the above-mentioned resin materials other than the resin material having a polar group. The surface coating layer may contain the above-mentioned additives.

[0046] The ratio of the thickness of the surface coat layer to the total thickness of the polypropylene stretched substrate and the surface coat layer is preferably 0.08% or more, more preferably 0.2% or more, even more preferably 1% or more, and also preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 5% or less, for example, 0.08% or more and 20% or less. The thickness of the surface coat layer is preferably 0.02 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and also preferably 10 μm or less, more preferably 5 μm or less, for example, 0.02 μm or more and 10 μm or less. When the above ratio or thickness is the lower limit or more, for example, the adhesion of the inorganic oxide layer can be improved, the deterioration of the gas barrier property can be suppressed, and the laminate strength of the laminate can be improved. When the above ratio or thickness is the upper limit or less, for example, the processability of the barrier substrate and the recyclability of the laminate can be improved.

[0047] For example, polypropylene or a resin composition containing polypropylene is formed into a film using a T-die method, an inflation method, or the like to obtain a polypropylene substrate, and then the substrate is stretched. A coating liquid for forming a surface coating layer is applied to the obtained stretched substrate, and the substrate is dried, thereby producing a resin substrate having a polypropylene stretched substrate and a surface coating layer.

[0048] (Polypropylene layer, surface resin layer and adhesive resin layer) In another embodiment of the stretched substrate, the polypropylene layer contains polypropylene as a main component. The details of polypropylene are as described above, and will not be described in this section. The content of polypropylene in the polypropylene layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0049] The polypropylene layer may contain the above-mentioned resin materials other than polypropylene. The polypropylene layer may contain the additives described above.

[0050] The polypropylene layer may have a single-layer structure or a multi-layer structure. The thickness of the polypropylene layer is preferably 10 μm or more, more preferably 15 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less.

[0051] The surface resin layer contains a resin material having a melting point of 180° C. or higher (hereinafter also referred to as a “high melting point resin material”). By providing a surface resin layer containing a high melting point resin material between a polypropylene layer and an inorganic oxide layer, for example, it is possible to improve the adhesion of the inorganic oxide layer formed on the surface resin layer and also to suppress a decrease in gas barrier properties. Furthermore, a packaging bag produced using a laminate having the surface resin layer has high laminate strength. In one embodiment, the surface resin layer may be provided on the polypropylene layer, i.e., the surface resin layer may be adjacent to the polypropylene layer. In one embodiment, when the stretched substrate of another aspect has an adhesive resin layer between the polypropylene layer and the surface resin layer, the adhesive resin layer may be provided on the polypropylene layer, and the surface resin layer may be provided on the adhesive resin layer, i.e., the adhesive resin layer may be adjacent to the polypropylene layer, and the surface resin layer may be adjacent to the adhesive resin layer.

[0052] The melting point of the high melting point resin material is preferably 185°C or higher, more preferably 190°C or higher, and even more preferably 205°C or higher. When the melting point is equal to or higher than the lower limit, for example, the adhesion of the inorganic oxide layer can be improved, the deterioration of the gas barrier property can be suppressed, and the laminate strength of the laminate can be improved. The melting point of the high melting point resin material is preferably 265°C or lower, more preferably 260°C or lower, and even more preferably 250°C or lower. This can improve, for example, the film formability of the stretched substrate.

[0053] In this specification, the melting point of the high melting point resin material and the like is measured in accordance with JIS K7121:2012 (Method of measuring transition temperature of plastics). Specifically, a differential scanning calorimetry (DSC) device is used to measure a DSC curve at a heating rate of 10°C / min, and the melting peak temperature is determined as the melting point.

[0054] The high melting point resin material contained in the surface resin layer has a melting point TA, and the polypropylene contained in the polypropylene layer has a melting point TB, and the difference between the melting points TA and TB is preferably 20° C. or more. The difference between the melting points TA and TB is preferably 80° C. or less, and more preferably 60° C. or less. When the difference between the melting point TA and the melting point TB is equal to or greater than the lower limit, the adhesion between the surface resin layer and the inorganic oxide layer can be improved, the gas barrier property can be improved, and the laminate strength of the packaging bag can be improved. When the difference between the melting point TA and the melting point TB is equal to or less than the upper limit, the film formability of the stretched polypropylene substrate can be further improved.

[0055] The high melting point resin material preferably has a polar group. The polar group refers to a group containing one or more heteroatoms, and examples thereof include ester groups, epoxy groups, hydroxyl groups, amino groups, amide groups, urethane groups, carboxy groups, carbonyl groups, carboxylic anhydride groups, sulfo groups, thiol groups, and halogen groups. Among these, hydroxyl groups, ester groups, amino groups, amide groups, carboxy groups, and carbonyl groups are preferred, and amide groups are more preferred.

[0056] The high melting point resin material may have a melting point of 180° C. or higher, and examples of the high melting point resin material include polyolefin, vinyl resin, acrylic resin, polyamide, polyimide, polyester, cellulose resin, and ionomer resin. For example, a resin material having a melting point of 180° C. or higher and a polar group is preferable, and more preferable are ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyester, and polyamides such as nylon 6, nylon 6,6, MXD nylon, and amorphous nylon. By using such a resin material, the adhesion of the inorganic oxide layer formed on the surface resin layer can be significantly improved, and the deterioration of the gas barrier property can be effectively suppressed.

[0057] In one embodiment, the high melting point resin material is preferably polyamide. By using polyamide as the high melting point resin material, the deterioration of gas barrier property can be suppressed even after bending the laminate, and the heat resistance of the laminate can be improved. In addition, the deterioration of gas barrier property can be suppressed even after the laminate is subjected to retort treatment and boiling treatment described later. The high melting point resin material is more preferably nylon 6.

[0058] The content of the high melting point resin material in the surface resin layer is preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.

[0059] The surface resin layer may contain the above-mentioned resin materials other than the high melting point resin material. The surface resin layer may contain the above-mentioned additives. The surface resin layer may be subjected to the above-mentioned surface treatment.

[0060] The ratio of the thickness of the surface resin layer to the total thickness of the stretched substrate of another embodiment having a polypropylene layer and a surface resin layer is preferably 1% or more, more preferably 1.5% or more, and also preferably 10% or less, more preferably 5% or less, for example 1% or more and 10% or less. The thickness of the surface resin layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and also preferably 5 μm or less, more preferably 4 μm or less, for example 0.1 μm or more and 5 μm or less. When the above ratio or thickness is equal to or more than the lower limit, for example, the adhesion of the inorganic oxide layer can be improved, the deterioration of the gas barrier property can be suppressed, and the laminate strength of the laminate can be improved. When the above ratio or thickness is equal to or less than the upper limit, for example, the film-forming property and processability of the stretched substrate of another embodiment, and the recyclability of the laminate can be improved.

[0061] The stretched substrate of another embodiment may have an adhesive resin layer between the polypropylene layer and the surface resin layer. This can improve the adhesion between these layers. The thickness of the adhesive resin layer is, for example, 1 μm or more and 15 μm or less. By making the thickness of the adhesive resin layer equal to or more than the lower limit, the adhesion between the polypropylene layer and the surface resin layer can be further improved. By making the thickness of the adhesive resin layer equal to or less than the upper limit, the processability of the barrier substrate can be improved. The adhesive resin layer can be formed, for example, by an adhesive resin. Examples of adhesive resins include polyether, polyester, polyurethane, silicone resin, epoxy resin, vinyl resin, phenol resin, polyolefin, and acid-modified polyolefin. Among these, polyolefin and its acid-modified polyolefin are preferred from the viewpoint of recyclability of the laminate, and polypropylene and its acid-modified polyolefin are more preferred. As the polypropylene used for the adhesive resin layer, commercially available products can be used, for example, the Admer series manufactured by Mitsui Chemicals, Inc. can be used.

[0062] (Inorganic oxide layer) The barrier substrate comprises an inorganic oxide layer. The inorganic oxide layer contains one or more inorganic oxides, for example, a vapor-deposited film of an inorganic oxide. A laminate comprising a barrier substrate has excellent gas barrier properties, specifically, oxygen barrier properties and water vapor barrier properties. A packaging bag produced using such a laminate can suppress oxidation deterioration of the contents filled in the packaging bag, and suppress the mass loss of the contents. The barrier substrate may, for example, comprise an inorganic oxide layer on a surface coat layer, or may comprise an inorganic oxide layer on a surface resin layer.

[0063] Examples of inorganic oxides include aluminum oxide (alumina), silicon oxide (silica), magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, barium oxide, and silicon carbide oxide (carbon-containing silicon oxide). Among these, silica, silicon carbide oxide, and alumina are preferred.

[0064] In one embodiment, the inorganic oxide is more preferably silica since no aging treatment is required after the formation of the inorganic oxide layer.In one embodiment, the inorganic oxide is more preferably carbon-containing silicon oxide since the deterioration of the gas barrier property can be suppressed even when the laminate is bent.

[0065] The thickness of the inorganic oxide layer is preferably 1 nm or more, more preferably 5 nm or more, even more preferably 10 nm or more, and is preferably 150 nm or less, more preferably 60 nm or less, even more preferably 40 nm or less, for example, 1 nm or more and 150 nm or less. A laminate having an inorganic oxide layer whose thickness is equal to or greater than the lower limit has, for example, excellent oxygen barrier properties and water vapor barrier properties. A laminate having an inorganic oxide layer whose thickness is equal to or less than the upper limit can, for example, suppress the occurrence of cracks in the inorganic oxide layer and has excellent recyclability.

[0066] The surface of the inorganic oxide layer may be subjected to the above-mentioned surface treatment.

[0067] Methods for forming inorganic oxide layers, particularly inorganic oxide vapor deposition films, include, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, as well as chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0068] The inorganic oxide layer may be a single layer formed by one deposition process, or may be a multilayer formed by multiple deposition processes. When the inorganic oxide layer is a multilayer, each layer may be composed of the same inorganic oxide or different inorganic oxides. Each layer may be formed by the same method or different methods.

[0069] The inorganic oxide layer is preferably a vapor-deposited film formed by a CVD method, and more preferably a carbon-containing silicon oxide vapor-deposited film formed by a CVD method. A laminate including such an inorganic oxide layer has, for example, excellent bending resistance.

[0070] The carbon-containing silicon oxide vapor deposition film contains silicon, oxygen and carbon. In one embodiment of the carbon-containing silicon oxide vapor deposition film, the carbon ratio C is preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and is preferably 50% or less, more preferably 40% or less, even more preferably 35% or less, for example, 3% or more and 50% or less, relative to 100% of the total of the three elements silicon, oxygen, and carbon. By setting the carbon ratio C in the above range, for example, even if the laminate is bent, the deterioration of the gas barrier property can be suppressed. In this specification, the ratio of each element is on a molar basis.

[0071] In one embodiment of the carbon-containing silicon oxide vapor deposition film, the silicon ratio Si is preferably 1% or more, more preferably 3% or more, even more preferably 8% or more, and is preferably 45% or less, more preferably 38% or less, even more preferably 33% or less, for example 1% or more and 45% or less, relative to the total of the three elements silicon, oxygen and carbon 100%. The oxygen ratio O is preferably 10% or more, more preferably 20% or more, even more preferably 25% or more, and is preferably 70% or less, more preferably 65% ​​or less, even more preferably 60% or less, for example 10% or more and 70% or less, relative to the total of the three elements silicon, oxygen and carbon 100%. By setting the silicon ratio Si and the oxygen ratio O in the above ranges, for example, even if the laminate is bent, the deterioration of the gas barrier property can be further suppressed.

[0072] In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the oxygen ratio O is preferably higher than the carbon ratio C, and the silicon ratio Si is preferably lower than the carbon ratio C. The oxygen ratio O is preferably higher than the silicon ratio Si, that is, the ratios are preferably in the order of O, C, and Si. This makes it possible to further suppress the deterioration of the gas barrier properties even when the laminate is bent, for example.

[0073] The proportions C, Si, and O in the carbon-containing silicon oxide vapor-deposited film are measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the following measurement conditions.

[0074] (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds, spectrum collected

[0075] (covering layer) The barrier substrate may further include a coating layer on the inorganic oxide layer. That is, the barrier substrate may further include a coating layer on the surface of the inorganic oxide layer opposite to the surface facing the stretched polypropylene substrate. A laminate including such a barrier substrate has, for example, excellent oxygen barrier properties and water vapor barrier properties. When the barrier substrate includes a coating layer, the coating layer may be adjacent to the first adhesive layer or the second adhesive layer.

[0076] In one embodiment, the coating layer contains a resin component. Examples of the resin component include polyolefins such as polyethylene, polypropylene, polybutene, and polymethylpentene, vinyl resins, acrylic resins, polyesters, urethane resins, melamine resins, and epoxy resins. The content of the resin component in the coating layer is preferably more than 50% by mass, more preferably 75% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, for example, more than 50% by mass and 95% by mass or less. The coating layer may contain the above-mentioned additives.

[0077] The thickness of the coating layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 1 μm or less, for example, 0.01 μm or more and 5 μm or less. Such a coating layer has, for example, excellent scratch resistance.

[0078] The coating layer can be formed, for example, by applying a coating liquid for the coating layer to the surface of the inorganic oxide layer and drying it. The coating liquid for the coating layer can be prepared, for example, by mixing the above-mentioned resin component and, if necessary, an additive and a solvent. Details of these components are as described above. Examples of the coating method for the coating liquid for the coating layer include known coating methods. Examples of the drying method for the applied coating liquid for the coating layer include methods that apply heat, such as hot air drying, hot roll drying, and infrared irradiation. The drying temperature may be 50°C or higher, or 150°C or lower.

[0079] In one embodiment, the coating layer may be a barrier coat layer containing a gas barrier resin. Examples of the gas barrier resin include ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyacrylonitrile, polyester, polyamide such as nylon 6, nylon 6,6 and polymetaxylylene adipamide, polyurethane, and acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, by including polyvinyl alcohol in the barrier coat layer, the occurrence of cracks in the inorganic oxide layer can be effectively prevented.

[0080] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 75% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, for example, 50% by mass or more and 95% by mass or less. Such a barrier coat layer has, for example, excellent gas barrier properties. The barrier coat layer may contain the above-mentioned additives.

[0081] The thickness of the barrier coat layer containing the gas barrier resin is preferably 0.01 μm or more, more preferably 0.1 μm or more, and also preferably 10 μm or less, more preferably 5 μm or less, for example, 0.01 μm or more and 10 μm or less. A barrier substrate having a barrier coat layer whose thickness is equal to or greater than the lower limit has, for example, excellent gas barrier properties. A barrier substrate having a barrier coat layer whose thickness is equal to or less than the upper limit can improve, for example, the processability and recyclability of the laminate. Furthermore, so long as the thickness of the barrier coat layer is within the above range, the recyclability is not impaired even if the gas barrier resin is a resin material other than polypropylene.

[0082] The barrier coat layer can be formed, for example, by dissolving or dispersing a material such as a gas barrier resin in water or an appropriate organic solvent, applying the resulting coating liquid to the surface of the inorganic oxide layer, and drying it. The barrier coat layer can also be formed, for example, by applying a commercially available barrier coating agent and drying it.

[0083] In one embodiment, the coating layer may be a gas barrier coating film formed by polycondensing a composition containing a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, and the like. A barrier substrate having a gas barrier coating film on an inorganic oxide layer has, for example, excellent gas barrier properties. The gas barrier coating film includes a hydrolysis polycondensate obtained by hydrolyzing and polycondensing the metal alkoxide or the like by a sol-gel method. By providing such a gas barrier coating film on an inorganic oxide layer, for example, the occurrence of cracks in the inorganic oxide layer can be effectively suppressed.

[0084] The metal alkoxide is represented, for example, by the formula (1). R 1 n M(OR 2 ) m (1) In formula (1), R 1 and R 2 each independently represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. 1 and R 2 In the above, examples of the organic group include alkyl groups having 1 to 8 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-hexyl, and n-octyl. The metal atom M is, for example, silicon, zirconium, titanium, or aluminum. Examples of the metal alkoxide include alkoxysilanes, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.

[0085] Examples of water-soluble polymers include hydroxyl group-containing polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymers. Depending on the desired physical properties such as oxygen barrier properties, water vapor barrier properties, water resistance, and weather resistance, either one of polyvinyl alcohol and ethylene-vinyl alcohol copolymers may be used, or both may be used in combination. Also, a gas barrier coating film obtained using polyvinyl alcohol and a gas barrier coating film obtained using an ethylene-vinyl alcohol copolymer may be laminated. The amount of water-soluble polymer used is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and preferably 500 parts by mass or less, relative to 100 parts by mass of metal alkoxide. By setting the content of the water-soluble polymer in the gas barrier coating film to the lower limit or more, the oxygen barrier properties and water vapor barrier properties of the laminate can be further improved. In addition, by setting the content of the water-soluble polymer in the gas barrier coating film to the upper limit or less, the film formability of the gas barrier coating film can be improved.

[0086] A silane coupling agent may be used together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used, and an organoalkoxysilane having an epoxy group is preferable, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned. The amount of the silane coupling agent used is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the metal alkoxide.

[0087] In the gas barrier coating film, the ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) is, by mass, preferably 4.5 or less, more preferably 3.5 or less, and also preferably 1.0 or more, more preferably 1.7 or more, for example, 1.0 or more and 4.5 or less. By setting the ratio of the metal alkoxide to the water-soluble polymer to be equal to or less than the upper limit, it is possible to suppress a decrease in the gas barrier property even after the laminate is bent. By setting the ratio of the metal alkoxide to the water-soluble polymer to be equal to or greater than the lower limit, the heat resistance of the laminate can be improved, and the deterioration of the gas barrier properties of the laminate can be suppressed even after the laminate is subjected to retort treatment and boiling treatment. The above ratio is a solid content ratio.

[0088] On the surface of the gas barrier coating film, the ratio of silicon atoms to carbon atoms (Si / C) measured by X-ray photoelectron spectroscopy (XPS) is preferably 1.60 or less, more preferably 1.35 or less, and is preferably 0.50 or more, more preferably 0.90 or more. By setting the ratio of silicon atoms to carbon atoms to be equal to or less than the upper limit, deterioration of the gas barrier properties can be suppressed even after the laminate is bent. By setting the ratio of silicon atoms to carbon atoms to the lower limit or more, the heat resistance of the laminate can be improved, and the deterioration of the gas barrier properties of the laminate can be suppressed even after the laminate is subjected to retort treatment and boiling treatment. The above range of the ratio of silicon atoms to carbon atoms can be achieved by appropriately adjusting the ratio of the metal alkoxide to the water-soluble polymer. In this specification, the ratio of silicon atoms to carbon atoms is based on moles.

[0089] The ratio of silicon atoms to carbon atoms by X-ray photoelectron spectroscopy (XPS) can be measured by narrow scan analysis under the following measurement conditions. (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds + 30 seconds + 60 seconds (total 120 seconds) and a spectrum was collected.

[0090] The gas barrier composition may contain water in an amount of preferably 0.1 mol or more, more preferably 0.5 mol or more, even more preferably 0.8 mol or more, and preferably 100 mol or less, more preferably 60 mol or less, even more preferably 2 mol or less, per mol of metal alkoxide. By making the water content equal to or greater than the lower limit, for example, the oxygen barrier property and water vapor barrier property of the laminate can be improved. By making the water content equal to or less than the upper limit, for example, the hydrolysis reaction can be carried out quickly.

[0091] The gas barrier composition may contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butyl alcohol.

[0092] The sol-gel catalyst is preferably an acid or an amine compound. Examples of the acid include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid; and organic acids such as acetic acid and tartaric acid. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less per mol of the total amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. By setting the amount of the acid to the lower limit or more, the catalytic effect can be improved. By setting the amount of the acid to the upper limit or less, the thickness of the gas barrier coating film formed can be made uniform.

[0093] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is suitable, such as N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferred. The amount of the amine compound used is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and also preferably 1.0 parts by mass or less, more preferably 0.3 parts by mass or less, based on 100 parts by mass of the total amount of the metal alkoxide and the silane coupling agent. By making the amount of the amine compound used equal to or more than the lower limit, the catalytic effect can be improved. By making the amount of the amine compound used equal to or less than the upper limit, the thickness of the gas barrier coating film formed can be made uniform.

[0094] Examples of methods for applying the gas barrier composition include roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, and applicator coating.

[0095] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. A gas barrier composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent. A polycondensation reaction gradually proceeds in the composition. The composition is applied on an inorganic oxide layer by a conventional method and dried. This drying causes further polycondensation of the metal alkoxide and the water-soluble polymer (and the silane coupling agent if the composition contains a silane coupling agent) to form a composite polymer layer. The above operation may be repeated to laminate a plurality of composite polymer layers. For example, the applied composition is heated at a temperature of preferably 20°C or higher, more preferably 50°C or higher, and even more preferably 70°C or higher, and also preferably 250°C or lower, more preferably 220°C or lower, even more preferably 150°C or lower, even more preferably 120°C or lower, and particularly preferably 100°C or lower, for 1 second to 10 minutes. This allows the formation of a gas barrier coating film.

[0096] The thickness of the gas barrier coating film is preferably 0.01 μm or more, more preferably 0.1 μm or more, and also preferably 100 μm or less, more preferably 10 μm or less, even more preferably 2 μm or less, still more preferably 1 μm or less, particularly preferably 0.5 μm or less, for example, 0.01 μm or more and 100 μm or less. This can, for example, prevent the deterioration of gas barrier properties, prevent the occurrence of cracks in the inorganic oxide layer, and improve the recyclability of the packaging bag.

[0097] <Print layer> The laminate of the present disclosure may have a printed layer on the surface of a substrate such as a first substrate and a second substrate. The image formed on the printed layer is not particularly limited, and may be a character, a pattern, a symbol, or a combination thereof. The printed layer may be formed using an ink derived from biomass. This can further reduce the environmental load.

[0098] Examples of methods for forming the printed layer include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of reducing the environmental load. The thickness of the printed layer is, for example, not less than 0.5 μm and not more than 3 μm.

[0099] <Sealant layer> The laminate of the present disclosure includes a sealant layer. The sealant layer contains polypropylene as a main component. The sealant layer contains the same type of resin material as the oriented polypropylene substrate, i.e., polypropylene as a main component. This allows the laminate to be made into a mono-material. In other words, after collecting used packaging bags, there is no need to separate the substrate and the sealant layer, improving the recyclability of the packaging bags.

[0100] The content of polypropylene in the sealant layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more. A laminate having such a sealant layer has, for example, excellent recyclability.

[0101] Examples of polypropylene include propylene homopolymers, propylene random copolymers such as propylene-α-olefin random copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. Details of the α-olefins are as described above. From the viewpoint of heat sealability, the density of polypropylene is, for example, 0.88 g / cm 3 More than 0.92g / cm 3 The density is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.). From the viewpoint of reducing the environmental load, biomass-derived polypropylene and / or recycled polypropylene may be used. The sealant layer may contain the above-mentioned additives.

[0102] The sealant layer may have a single-layer structure or a multi-layer structure. The thickness of the sealant layer is preferably 10 μm or more, more preferably 20 μm or more, and also preferably 200 μm or less, more preferably 150 μm or less, for example, 10 μm or more and 200 μm or less. A laminate having a sealant layer whose thickness is equal to or greater than the lower limit has, for example, excellent seal strength. A laminate having a sealant layer whose thickness is equal to or less than the upper limit has, for example, excellent processability. When a pouch (particularly a retort pouch) is produced from the laminate, the thickness of the sealant layer is preferably 30 μm or more, and also preferably 100 μm or less.

[0103] The composite elastic modulus of the sealant layer is preferably 900 MPa or less, more preferably 870 MPa or less, even more preferably 850 MPa or less, and also preferably 300 MPa or more, more preferably 400 MPa or more, even more preferably 500 MPa or more, for example, 300 MPa or more and 900 MPa or less. A packaging bag produced using a laminate having a sealant layer with a composite elastic modulus within the above range tends to have excellent impact resistance, and therefore excellent drop-breakage resistance.

[0104] The composite elastic modulus of the sealant layer is measured by a nanoindentation method. Specifically, a nanoindenter is used to measure the composite elastic modulus with the cross section of the sealant layer of the laminate as the measurement surface. The cross section is obtained by cutting the laminate in the thickness direction. The indenter is pressed into the sealant layer near the center in the thickness direction of the sealant layer among the exposed sections of the sealant layer. The measurement conditions are as follows. A Berkovich indenter (triangular pyramid indenter) is used as the indenter of the nanoindenter. The indenter is pressed into the sealant layer from the cross section of the sealant layer to a depth of 100 nm over a period of 3 seconds, held in that state for 5 seconds, and then unloaded over a period of 3 seconds, and the maximum load P max , contact projection area A at maximum depth p A load-displacement curve is obtained, and the composite elastic modulus is calculated from the load-displacement curve obtained by the following formula (1).

[0105]

number

[0106] The measurement is performed in a room temperature (23°C) environment. The measurement is performed at five or more points on the same cross section, and the composite elastic modulus is recorded as the arithmetic average value of the values ​​measured at five points with good reproducibility. Details of the measurement conditions are described in the Examples section.

[0107] When the sealant layer contains a propylene block copolymer, the composite modulus of elasticity of the sealant layer can be adjusted by the content of ethylene-propylene rubber (EPR). Specifically, the higher the content of ethylene-propylene rubber (EPR), the lower the composite modulus of elasticity can be, and the lower the content of ethylene-propylene rubber (EPR), the higher the composite modulus of elasticity can be. Furthermore, when the sealant layer contains a propylene block copolymer, the composite elastic modulus of the sealant layer can be adjusted by the content of additives such as polyethylene, elastomer, etc. Specifically, the higher the content of the additive, the lower the composite elastic modulus can be, and the lower the content of the additive, the higher the composite elastic modulus can be.

[0108] The value obtained by dividing the composite elastic modulus of the sealant layer by the thickness of the sealant layer is preferably 1.5 MPa / μm or more, more preferably 5 MPa / μm or more, and even more preferably 10 MPa / μm or more. The value obtained by dividing the composite elastic modulus of the sealant layer by the thickness of the sealant layer is preferably less than 90 MPa / μm, and also preferably 60 MPa / μm or less, and more preferably 30 MPa / μm or less. The value obtained by dividing the composite elastic modulus of the sealant layer by the thickness of the sealant layer is, for example, 1.5 MPa / μm or more and less than 90 MPa / μm. A laminate having such a sealant layer tends to have excellent tearability, and a packaging bag produced using the laminate tends to have excellent openability.

[0109] From the viewpoint of heat sealability, the sealant layer is preferably an unstretched polypropylene film, and the unstretched polypropylene film can be produced by utilizing, for example, a cast method, a T-die method, an inflation method, or the like. The sealant layer may be subjected to the above-mentioned surface treatment.

[0110] <Adhesive layer> The laminate of the present disclosure comprises a first adhesive layer between a first substrate and a second substrate. The laminate of the present disclosure comprises a second adhesive layer between the second substrate and a sealant layer. Such a laminate has, for example, excellent lamination strength between the first substrate / second substrate and between the second substrate / sealant layer.

[0111] (First adhesive layer) The elastic modulus of the cross section of the first adhesive layer measured with an atomic force microscope (AFM) is 30.0 MPa or more, preferably 33.0 MPa or more, and more preferably 35.0 MPa or more. A laminate having a second adhesive layer with an elastic modulus equal to or more than the lower limit and a thickness of 0.5 μm to 3.0 μm tends to have excellent tearability, and a packaging bag produced using the laminate tends to have excellent openability.

[0112] The elastic modulus of the cross section of the first adhesive layer measured using AFM is preferably 120 MPa or less, more preferably 110 MPa or less, even more preferably 100 MPa or less, still more preferably 90.0 MPa or less, particularly preferably 80.0 MPa or less, 70.0 MPa or less, 60.0 MPa or less, or 50.0 MPa or less. A laminate having a first adhesive layer with an elastic modulus of the upper limit or less tends to have excellent laminate strength. The elastic modulus of the first adhesive layer is, for example, 30.0 MPa or more and 120 MPa or less. Details of the conditions for measuring the elastic modulus by AFM will be described in the Examples section.

[0113] The first adhesive layer having the above elastic modulus can be formed, for example, by using a solvent-free adhesive described below and appropriately changing the type and molecular weight of the polymer component contained in the base agent, the type of curing agent, the molar ratio (NCO / OH), and the aging conditions, each of which will be described below.

[0114] The thickness of the first adhesive layer is 3.0 μm or less, preferably 2.5 μm or less, more preferably 2.0 μm or less, even more preferably 1.5 μm or less, and also 0.5 μm or more, preferably 0.8 μm or more, more preferably 1.0 μm or more, for example, 0.5 μm or more and 3.0 μm or less. A laminate having a first adhesive layer with an elastic modulus of 30.0 MPa or more and a thickness of the upper limit or less tends to have excellent tearability, and a packaging bag made using the laminate tends to have excellent openability. A laminate having a first adhesive layer with an elastic modulus of 30.0 MPa or more and a thickness of the lower limit or more tends to have excellent tearability, and a packaging bag made using the laminate tends to have excellent openability.

[0115] Furthermore, when the thickness of the first adhesive layer is equal to or less than the upper limit, the productivity of the laminate including the first adhesive layer can be improved for the following reasons. A typical method for producing the laminate of the present disclosure is to produce a raw roll by bonding a first substrate and a second substrate via a first adhesive layer, and then to bond the raw roll and a sealant layer via a second adhesive layer. The raw roll produced by bonding a first substrate and a second substrate via a first adhesive layer having a thickness of less than or equal to the upper limit has a small thickness, so that the roll diameter is not likely to become large when wound into a roll, and it is easy to make the raw roll longer. As the raw roll becomes longer, the time loss in switching from the process of bonding the first substrate and the second substrate to the process of bonding the raw roll and the sealant layer is reduced, and as a result, the productivity of the laminate can be improved.

[0116] The thickness of the first adhesive layer relative to the total thickness of the laminate is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1.0% or more, and is preferably 3.0% or less, more preferably 2.5% or less, even more preferably 2.0% or less, even more preferably 1.5% or less, for example, 0.5% or more and 3.0% or less.

[0117] When the elastic modulus of the first adhesive layer is equal to or higher than a certain level, the laminate including the first adhesive layer exhibits excellent tear resistance. The reason for this is believed to be as follows. The elastic modulus is generally an index of the resistance of an object to deformation, and the higher the elastic modulus, the less the object is likely to deform. In addition, when the laminate is torn, it is generally torn in order from the first substrate constituting the outer side of the laminate toward the sealant layer. If the elastic modulus of the first adhesive layer present between the first substrate and the second substrate is a certain level or higher (for example, 30 MPa or higher), the first adhesive layer is less likely to deform, and when a force is applied to the first substrate, the force is easily transmitted to the second substrate, the second adhesive layer, and the sealant layer through the first adhesive layer. That is, the force that tears the first substrate is easily transmitted to the second substrate and other layers, and is easily acted as a force that tears other layers. As a result, the laminate as a whole is easily torn, and it is considered that the tearability of the laminate is excellent.

[0118] In one embodiment, the value obtained by dividing the elastic modulus of the first adhesive layer by the thickness of the first adhesive layer is preferably 10 MPa / μm or more, more preferably 15 MPa / μm or more, and even more preferably 25 MPa / μm or more. The value obtained by dividing the elastic modulus of the first adhesive layer by the thickness of the first adhesive layer is preferably 240 MPa / μm or less, and also preferably 100 MPa / μm or less, and more preferably 50 MPa / μm or less. The value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is, for example, 10 MPa / μm or more and 240 MPa / μm or less. A laminate having such a first adhesive layer tends to have excellent tearability, and a packaging bag produced using the laminate tends to have excellent openability.

[0119] (Second adhesive layer) The thickness of the second adhesive layer is preferably 0.5 μm or more, more preferably 0.8 μm or more, even more preferably 1.0 μm or more, particularly preferably 3.0 μm or more, and is preferably 10.0 μm or less, more preferably 8.0 μm or less, even more preferably 6.0 μm or less, particularly preferably 5.0 μm or less, for example, 0.5 μm or more and 10.0 μm or less. A laminate having a second adhesive layer whose thickness is equal to or more than the lower limit can suppress elongation of the sealant layer when torn.

[0120] In one embodiment (A), the elastic modulus measured by AFM for the cross section of the second adhesive layer is preferably less than 30.0 MPa, more preferably 28.0 MPa or less, even more preferably 26.0 MPa or less, and also preferably 5.0 MPa or more, more preferably 10.0 MPa or more, even more preferably 15.0 MPa or more, even more preferably 16.0 MPa or more, particularly preferably 18.0 MPa or more, for example, 5.0 MPa or more and less than 30.0 MPa. A packaging bag produced using a laminate having a second adhesive layer having such an elastic modulus tends to be able to suppress the deterioration of gas barrier properties even after heat treatment such as retort treatment. The second adhesive layer having such an elastic modulus can be formed, for example, by using a solvent-based adhesive described later, and by appropriately changing the type and molecular weight of the polymer component contained in the main agent, the type of curing agent, the molar ratio (NCO / OH), and the aging conditions described later.

[0121] When the second adhesive layer has the elastic modulus of one embodiment (A), the elastic modulus of the second adhesive layer is smaller than that of the first adhesive layer. The laminate of this embodiment has better tearability, and the packaging bag made using the laminate tends to have better openability. The reason for this is considered to be as follows. When a packaging bag is produced using a laminate having a sealant layer, it is common to stack two laminates so that the sealant layers face each other, and heat seal the ends of the laminate to produce the packaging bag. When the packaging bag is opened, the two laminates are torn apart in a stacked state. Here, if one of the two laminates is the "front laminate" and the other is the "rear laminate," the front laminate is torn from the first substrate toward the sealant layer, while the rear laminate is torn from the sealant layer toward the first substrate. As mentioned above, the composite elastic modulus of the sealant layer is preferably below a certain level (for example, 900 MPa or less), and since the sealant layer is easily deformed, when the laminate on the back side is torn, the sealant layer is first stretched to a certain extent and then torn, and then the other layers are torn in order. If the elastic modulus of the second adhesive layer is below a certain level (for example, less than 30.0 MPa), the second adhesive layer is easily deformed, the second adhesive layer follows the elongation of the sealant layer, and the force tearing the sealant layer is easily transmitted to the second substrate, the first adhesive layer, and the first substrate via the second adhesive layer. That is, in the laminate on the back side, the force tearing the sealant layer is easily transmitted to the second substrate and other layers, and is easily acted as a force tearing other layers. As a result, the laminate on the back side is also easily torn, and it is considered that the tearability of the entire laminate of two layers is excellent.

[0122] When the second adhesive layer has the elastic modulus of one embodiment (A), the thickness of the second adhesive layer is, in one embodiment, preferably 1.0 μm or more, more preferably 1.5 μm or more, even more preferably 2.0 μm or more, particularly preferably 2.5 μm or more, and also preferably 10.0 μm or less, more preferably 8.0 μm or less, even more preferably 6.0 μm or less, particularly preferably 5.0 μm or less, for example 1.0 μm or more and 10.0 μm or less. In this embodiment, the thickness of the second adhesive layer relative to the thickness of the entire laminate is preferably 1.0% or more, more preferably 1.5% or more, even more preferably 2.0% or more, particularly preferably 2.5% or more, and also preferably 10.0% or less, more preferably 8.0% or less, even more preferably 6.0% or less, particularly preferably 5.0% or less, for example 1.0% or more and 10.0% or less. A laminate having a second adhesive layer having a thickness equal to or greater than the lower limit tends to have excellent laminate strength even after heat treatment.

[0123] When the second adhesive layer has the elastic modulus of one embodiment (A), the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer in one embodiment. When a printed layer is provided on the surface of the first substrate facing the first adhesive layer, the first adhesive layer can well cover the step caused by the printed layer, and there is a tendency that a packaging bag with good appearance can be obtained. The ratio of the thickness 1 of the first adhesive layer to the thickness 2 of the second adhesive layer (thickness 1 / thickness 2) may be, for example, 0.4 or more, 0.6 or more, or 0.8 or more. When the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer, it may be more than 1.0, and may be 2.5 or less, 1.8 or less, or 1.2 or less.

[0124] When the second adhesive layer has the elastic modulus of one embodiment (A), in one embodiment, the value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is preferably 0.5 MPa / μm or more, more preferably 1 MPa / μm or more, and even more preferably 2 MPa / μm or more. The value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is preferably less than 30 MPa / μm, and also preferably 15 MPa / μm or less, and more preferably 10 MPa / μm or less. The value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is, for example, 0.5 MPa / μm or more and less than 30 MPa / μm. A laminate having such a second adhesive layer tends to have better tearability, and a packaging bag produced using the laminate tends to have better openability.

[0125] In one embodiment (B), the elastic modulus measured by AFM on the cross section of the second adhesive layer is preferably 30.0 MPa or more, more preferably 33.0 MPa or more, even more preferably 35.0 MPa or more, and is preferably 120 MPa or less, more preferably 110 MPa or less, even more preferably 100 MPa or less, even more preferably 90.0 MPa or less, particularly preferably 80.0 MPa or less, 70.0 MPa or less, 60.0 MPa or less, or 50.0 MPa or less, for example, 30.0 MPa or more and 120 MPa or less. A laminate having a second adhesive layer with an elastic modulus of less than the upper limit tends to have excellent laminate strength. The second adhesive layer having such an elastic modulus can be formed, for example, by using a solvent-free adhesive described later, and by appropriately changing the type and molecular weight of the polymer component contained in the base agent, the type of the curing agent, the molar ratio (NCO / OH), and the aging conditions described later.

[0126] When the second adhesive layer has the elastic modulus of one embodiment (B), the thickness of the second adhesive layer is, in one embodiment, preferably 3.0 μm or less, more preferably 2.5 μm or less, even more preferably 2.0 μm or less, even more preferably 1.5 μm or less, and also preferably 0.5 μm or more, more preferably 0.8 μm or more, even more preferably 1.0 μm or more, for example 0.5 μm or more and 3.0 μm or less. In this embodiment, the thickness of the second adhesive layer relative to the thickness of the entire laminate is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1.0% or more, and also preferably 3.0% or less, more preferably 2.5% or less, even more preferably 2.0% or less, even more preferably 1.5% or less, for example 0.5% or more and 3.0% or less. In one embodiment, the thickness of the second adhesive layer is smaller than the thickness of the first adhesive layer. A packaging bag made using such a laminate having a second adhesive layer tends to have excellent impact resistance, and therefore excellent resistance to dropping and breaking, as well as excellent tearability, and therefore excellent openability. In addition, the packaging bag has excellent recyclability, for example.

[0127] When the second adhesive layer has the elastic modulus of one embodiment (B), in one embodiment, the value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is preferably 10 MPa / μm or more, more preferably 15 MPa / μm or more, and even more preferably 25 MPa / μm or more. The value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is preferably 240 MPa / μm or less, and also preferably 100 MPa / μm or less, and more preferably 50 MPa / μm or less. The value obtained by dividing the elastic modulus of the second adhesive layer by the thickness of the second adhesive layer is, for example, 10 MPa / μm or more and 240 MPa / μm or less.

[0128] (glue) The first adhesive layer and the second adhesive layer are each composed of an adhesive. The adhesive forming the first adhesive layer and the adhesive forming the second adhesive layer may be the same or different. The adhesive may be any of a one-component curing adhesive, a two-component curing adhesive, and a non-curing adhesive, and a two-component curing adhesive is preferred from the viewpoint of easily adjusting the elastic modulus to the above-mentioned range.

[0129] A method for obtaining a laminate using an adhesive includes applying an adhesive to an object, superposing another object on the formed adhesive layer, and allowing the adhesive layer sandwiched between the two to harden. Examples of the object include a first substrate, a second substrate, and a sealant film. The process of allowing the adhesive layer to harden is also referred to as the "aging process" below.

[0130] The aging conditions of the adhesive are described below. The aging temperature is preferably 25°C or higher, more preferably 30°C or higher, and even more preferably 35°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 60°C or lower. The aging time is preferably 5 hours or higher, more preferably 10 hours or higher, and even more preferably 20 hours or higher, and is preferably 150 hours or lower, more preferably 135 hours or lower, and even more preferably 120 hours or lower. By increasing the aging temperature, the elastic modulus of the adhesive layer tends to increase. By increasing the aging time, the elastic modulus of the adhesive layer tends to increase.

[0131] Examples of adhesives include polyurethane adhesives, polyester adhesives, polyether adhesives, rubber adhesives, vinyl adhesives, olefin adhesives, silicone adhesives, epoxy adhesives, and phenol adhesives. Among these, from the viewpoint of easily adjusting the elastic modulus to the above-mentioned range, polyurethane adhesives, polyester adhesives, and polyether adhesives are preferred, polyurethane adhesives and polyester adhesives are more preferred, polyurethane adhesives are even more preferred, and two-liquid curing polyurethane adhesives are particularly preferred.

[0132] The adhesive may be a solvent-based adhesive or a solventless adhesive. A solvent-based adhesive is an adhesive used in a method in which the adhesive is applied to an object, heated in an oven or the like to volatilize the solvent in the adhesive, and then the adhesive is bonded to another object. In the case of a two-liquid curing adhesive, either the base agent or the curing agent, or both, contain a solvent. Examples of the solvent include organic solvents, specifically, hydrocarbon solvents such as toluene, xylene, n-hexane, and methylcyclohexane; ester solvents such as ethyl acetate, n-propyl acetate, n-butyl acetate, and isobutyl acetate; alcohol solvents such as methanol, ethanol, isopropyl alcohol, n-butyl alcohol, and isobutyl alcohol; and ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0133] A solvent-free adhesive is an adhesive that is applied to an object and then bonded to another object without necessarily going through a process of heating in an oven or the like to volatilize the solvent. In the case of a two-component curing adhesive, both the base agent and the curing agent are substantially free of solvent. "Substantially free of solvent" includes cases where the solvent used as a reaction medium during the manufacture of the adhesive's components, or the base agent and / or curing agent in the case of a two-component curing adhesive, is not completely removed, leaving trace amounts of solvent remaining in the adhesive, or the base agent and / or curing agent in the case of a two-component curing adhesive.

[0134] The two-component curing polyurethane adhesive has a base agent and a curing agent. The two-component curing polyurethane adhesive may be a solvent-based adhesive or a solventless adhesive. The two-component curing polyurethane adhesive will be described below.

[0135] The polyurethane adhesive has, for example, a base agent containing a polyol compound and a curing agent containing a polyisocyanate compound. Examples of the cured product (reaction product) formed by mixing such a base agent and a curing agent include polyurethane, specifically polyester polyurethane, polyether polyurethane, polycarbonate polyurethane, and acrylic polyurethane.

[0136] The polyol compound has two or more hydroxyl groups in one molecule. Examples of the polyol compound include polyester polyurethane polyol, polyester polyol, polyether polyol, polycarbonate polyol and acrylic polyol. Among these, polyester polyurethane polyol and polyester polyol are preferred from the viewpoint of easily obtaining an adhesive layer having an elastic modulus in the above-mentioned range, and in the case of a solvent-based adhesive, polyester polyurethane polyol is more preferred, and in the case of a solventless adhesive, polyester polyol is more preferred.

[0137] Polyester polyurethane polyol is a compound having two or more hydroxy groups, ester bonds, and urethane bonds in one molecule, and has, for example, a polyester polyurethane structure as the main skeleton. Polyester polyol is a compound having two or more hydroxy groups and ester bonds in one molecule, and has, for example, a polyester structure as the main skeleton. Polyether polyol is a compound having two or more hydroxy groups and ether bonds in one molecule. Polycarbonate polyol is a compound having two or more hydroxy groups and carbonate bonds in one molecule.

[0138] The weight average molecular weight (Mw) of the polymer component (e.g., polyol compound) contained in the base of the two-component curing and solvent-based adhesive is, from the viewpoint of coatability, preferably 11,000 or more, more preferably 13,000 or more, even more preferably 15,000 or more, even more preferably 18,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 50,000 or less, and even more preferably 40,000 or less. The smaller the Mw, the higher the elastic modulus of the adhesive layer tends to be, and the larger the Mw, the lower the elastic modulus of the adhesive layer tends to be. The polydispersity (Mw / Mn) of the polymer component (e.g., polyol compound) contained in the base agent is preferably 5.0 or less, more preferably 4.5 or less, and even more preferably 4.0 or less, and is preferably 1.5 or more, more preferably 2.0 or more, and even more preferably 2.5 or more, where Mn is the number average molecular weight of the polymer component (e.g., polyol compound) contained in the base agent. Each average molecular weight is measured by gel permeation chromatography (GPC) in accordance with JIS K7252-1:2016, and is expressed as a polystyrene equivalent value. For the GPC measurement, the measurement device was HLC-8220GPC (manufactured by Tosoh Corporation), and the column was TSKgel GHM HQ -H and TSK guardcolumn H HQ -H connected in series, and dimethylformamide (DMF) can be used as the eluent.

[0139] From the viewpoint of coatability, the weight average molecular weight (Mw) of the polymer component (e.g., polyol compound) contained in the base agent of the two-component curing solventless adhesive is preferably 800 or more, more preferably 1,200 or more, and even more preferably 2,000 or more, and is preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 6,000 or less. The smaller the Mw, the higher the elastic modulus of the adhesive layer tends to be, and the larger the Mw, the lower the elastic modulus of the adhesive layer tends to be. The polydispersity (Mw / Mn) of the polymer component (e.g., polyol compound) contained in the base agent is preferably 2.8 or less, more preferably 2.7 or less, even more preferably 2.6 or less, particularly preferably 2.5 or less, and is preferably 1.2 or more, more preferably 1.5 or more, and even more preferably 2.0 or more, where Mn is the number average molecular weight of the polymer component (e.g., polyol compound) contained in the base agent.

[0140] The polyisocyanate compound has two or more isocyanate groups in one molecule. Examples of the polyisocyanate compound include aromatic isocyanates and aliphatic isocyanates. The polyisocyanate compound may be a blocked isocyanate compound obtained by addition reaction using a known isocyanate blocking agent by a known and conventional appropriate method.

[0141] Examples of polyisocyanate compounds include aliphatic isocyanate compounds such as tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), norbornene diisocyanate, and isophorone diisocyanate (IPDI); aromatic isocyanate compounds such as diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate, tolylene diisocyanate (TDI), naphthalene diisocyanate, and α,α,α',α'-tetramethyl-m-xylylene diisocyanate, dimers and trimers (e.g., isocyanurate bodies) derived from these compounds; and adducts, biuret bodies, and allophanate bodies obtained by reacting these compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds.

[0142] Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexamethylene glycol, 1,8-octamethylene glycol, 1,4-cyclohexanedimethanol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolethane, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine and metaxylylenediamine, and trimethylolpropane is preferred. Examples of high molecular weight active hydrogen compounds include polyester, polyether polyol and polyamide.

[0143] The base agent containing a polyol compound and the curing agent containing a polyisocyanate compound are preferably used in such an amount ratio that the molar ratio (NCO / OH) between the total isocyanate groups of the polyisocyanate compound and the total hydroxyl groups of the polyol compound is as follows. That is, the molar ratio (NCO / OH) is preferably 0.5 or more, more preferably 1.0 or more, even more preferably 1.5 or more, and is preferably 8.0 or less, more preferably 6.0, even more preferably 5.0 or less, and in the case of a solventless adhesive, it is even more preferably 4.0 or less, particularly preferably 3.0 or less. The larger the molar ratio (NCO / OH), the higher the elastic modulus of the adhesive layer tends to be, and the smaller the molar ratio (NCO / OH), the lower the elastic modulus of the adhesive layer tends to be.

[0144] [Packaging bag] The laminate of the present disclosure is preferably used as a packaging material. The packaging material is used to produce a packaging bag. The packaging bag of the present disclosure includes the laminate. By using the laminate of the present disclosure as a packaging material, a packaging bag can be produced. In one embodiment, the laminate of the present disclosure is folded in half and stacked so that the first substrate is located on the outside and the sealant layer is located on the inside, and the ends and the like are heat-sealed to produce a packaging bag. In another embodiment, a plurality of laminates of the present disclosure are stacked so that the sealant layers face each other, and the ends and the like are heat-sealed to produce a packaging bag. The entire packaging bag may be composed of the laminate, or a part of the packaging bag may be composed of the laminate.

[0145] Examples of packaging bags include packaging bags of various shapes such as standing pouch type, side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, grooving seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, gusset type, etc. Examples of heat sealing methods include bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.

[0146] The packaging bag may have an easy-to-open portion. Examples of the easy-to-open portion include a notch portion that serves as a starting point for tearing the packaging bag, and a half-cut line formed by laser processing or a cutter as a path for tearing the packaging bag.

[0147] The packaging bag may include a steam release mechanism. The steam release mechanism is configured to communicate between the inside and outside of the packaging bag when the steam pressure inside the packaging bag reaches or exceeds a predetermined value, to release steam, and to suppress steam from escaping at locations other than the steam release mechanism. The steam release mechanism includes, for example, a steam release seal portion protruding from the side seal portion toward the inside of the packaging bag, and a non-seal portion isolated from the content storage portion by the steam release seal portion. The non-seal portion communicates with the outside of the packaging bag. The packaging bag filled with the content and with the opening heat-sealed is heated using a microwave oven or the like. This increases the internal pressure, causing the steam release seal portion to peel off. Steam passes through the peeled portion of the steam release seal portion and the non-seal portion to escape to the outside of the packaging bag.

[0148] The contents to be contained in the packaging bag include, for example, liquids, solids, powders, and gels. The contents may be food or beverages, or non-food or beverages such as chemicals, cosmetics, medicines, metal parts, and electronic parts. After the contents are contained in the packaging bag, the opening of the packaging bag can be heat-sealed to seal the packaging bag. The contents may be a retort food or a boiled food. The packaging bag of the present disclosure may be a pouch for containing a retort food or a boiled food.

[0149] As specific examples of packaging bags, a small bag and a standing pouch will be described below. A sachet is a small packaging bag used to hold contents of, for example, 1 g to 200 g. Contents that can be held in a sachet include, for example, sauces, soy sauce, dressings, ketchup, syrups, cooking alcohol, and other liquid or viscous seasonings; liquid soups, powdered soups, fruit juices, spices, pet food, liquid beverages, jelly-like beverages, instant foods, and other foods and beverages; and non-food items such as chemicals, cosmetics, pharmaceuticals, metal parts, and electronic parts.

[0150] The stand-up pouch is used to store contents of, for example, 50 g to 2000 g. Examples of contents that can be stored in the stand-up pouch include shampoo, rinse, conditioner, hand soap, body soap, air freshener, deodorant, insect repellent, detergent, dressing, edible oil, mayonnaise, other liquid or viscous seasonings, liquid beverages, jelly-like beverages, instant foods, other foods and beverages, pet foods, creams, metal parts, and electronic parts.

[0151] In one embodiment, the contents of the packaging bag is pet food.

[0152] In one embodiment, the packaging bag of the present disclosure is suitable as a retort-treated pouch (hereinafter also referred to as a "retort pouch") or a boiled pouch (hereinafter also referred to as a "boiled pouch"), or as a microwave-compatible packaging bag, since the packaging bag of the present disclosure can suppress deterioration of gas barrier properties even when subjected to heat treatment. The packaging bag of the present disclosure is also suitable as a boiled or retort pouch for microwave ovens. Here, the microwave-compatible packaging bag means a packaging bag that can be heated using a microwave oven.

[0153] A retort pouch is a packaging bag that is filled with food or drink, sealed, and then heat sterilized (retort processing) with water or steam at a temperature exceeding 100°C under pressure. A boil pouch is a packaging bag that is filled with food or drink, sealed, and then boiled at a temperature of 100°C or less.

[0154] In one embodiment, the packaging bag of the present disclosure is a retort pouch. There are various conditions for the retort treatment, but any pouch that has undergone general retort treatment is included in the retort pouch. Among the retort treatments, for example, a treatment temperature of 105°C or higher and 115°C or lower may be called semi-retort treatment, a treatment temperature of more than 115°C and 121°C or lower may be called retort treatment, and a treatment temperature of more than 121°C and 140°C or lower may be called high retort treatment. The retort treatment time is, for example, from 5 minutes to 60 minutes, and preferably from 15 minutes to 40 minutes.

[0155] In one embodiment, the packaging bag of the present disclosure is a retort pouch. The oxygen permeability (unit: cc / m 2 In one embodiment, the oxygen permeability (day atm) is preferably 2.0 or less, more preferably 1.5 or less, further preferably 1.3 or less, and particularly preferably 1.0 or less. The oxygen permeability is measured in accordance with JIS K7126-2:2006 at a temperature of 23°C and a relative humidity of 90%. The lower limit of the oxygen permeability is preferably as low as possible, but may be, for example, 0.1.

[0156] 18 shows a packaging bag 50 obtained by bonding two laminates together. The shaded areas indicate the heat-sealed areas. The packaging bag 50 may have an easy-to-open part 51. Examples of the easy-to-open part 51 include a notch part 52 that serves as a starting point for tearing, and a half-cut line 53 formed by laser processing or a cutter as a path for tearing.

[0157] FIG. 19 shows a simplified example of the configuration of a standing pouch. The shaded areas indicate the heat-sealed areas. In one embodiment, the standing pouch 60 comprises a body portion (side sheets) 61 and a bottom portion (bottom sheet) 62. The side sheets 61 and the bottom sheet 62 may be made of the same material or different materials. The bottom sheet 62 retains the shape of the side sheets 61, thereby imparting self-supporting properties to the pouch, and the pouch can be made into a standing pouch. A storage space for storing contents is formed within the area surrounded by the side sheets 61 and the bottom sheet 62.

[0158] The standing pouch 60 may include a steam release mechanism 63. The steam release mechanism 63 includes a steam release seal portion 63a protruding from the side seal portion toward the inside of the packaging bag, and a non-sealed portion 63b isolated from the content storage portion by the steam release seal portion 63a. The non-sealed portion 63b communicates with the outside of the packaging bag.

[0159] In the stand-up pouch, only the body portion may be made of the laminate of the present disclosure, only the bottom portion may be made of the laminate, or both the body portion and the bottom portion may be made of the laminate.

[0160] In one embodiment, the side sheet can be formed by making a bag so that the sealant layer of the laminate of the present disclosure is the innermost layer. In one embodiment, the side sheet can be formed by preparing two sheets of the laminate of the present disclosure, overlapping them so that the sealant layers face each other, and heat-sealing the side edges on both sides to make a bag.

[0161] In another embodiment, the side sheet can be formed by preparing two laminates of the present disclosure, overlapping them with the sealant layers facing each other, inserting two laminates folded in a V-shape with the sealant layers facing outward between the laminates at the side edges on both sides of the overlapped laminates, and heat sealing them. According to this production method, a standing pouch having a body with side gussets can be obtained.

[0162] In one embodiment, the bottom sheet can be formed by inserting the laminate between the lower parts of the side sheets that have been made into a bag, and heat sealing the laminate. More specifically, the bottom sheet can be formed by inserting the laminate folded into a V shape with the sealant layer facing outward between the lower parts of the side sheets that have been made into a bag, and heat sealing the laminate.

[0163] In one embodiment, two laminates are prepared, and these are stacked with the sealant layers facing each other. Next, another laminate is folded in a V shape with the sealant layer facing outward, and this is sandwiched under the laminates that have been stacked, and heat sealed to form a bottom. Next, two sides adjacent to the bottom are heat sealed to form a body. In this manner, a standing pouch of one embodiment can be formed.

[0164] The present disclosure relates to, for example, the following [1] to

[14] . [1] A laminate comprising a first substrate, a first adhesive layer, a second substrate, a second adhesive layer, and a sealant layer in that order in the thickness direction, wherein the first substrate comprises an oriented substrate containing polypropylene as a main component, the second substrate comprises an oriented substrate containing polypropylene as a main component, the sealant layer contains polypropylene as a main component, the elastic modulus of the cross section of the first adhesive layer measured using an atomic force microscope (AFM) is 30.0 MPa or more, and the thickness of the first adhesive layer is 0.5 μm or more and 3.0 μm or less. [2] The laminate described in [1], wherein the elastic modulus of the cross section of the second adhesive layer measured using an atomic force microscope (AFM) is less than 30.0 MPa. [3] The laminate described in [2], wherein the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer. [4] The laminate described in [1], wherein the elastic modulus of the cross section of the second adhesive layer measured using an atomic force microscope (AFM) is 30.0 MPa or more. [5] The laminate described in [4], wherein the thickness of the second adhesive layer is smaller than the thickness of the first adhesive layer. [6] The laminate according to any one of the above [1] to [5], wherein the second adhesive layer has a thickness of 0.5 μm or more and 10.0 μm or less. [7] The laminate according to any one of the above [1] to [6], wherein at least one selected from the first substrate and the second substrate is a barrier substrate further comprising an inorganic oxide layer. [8] The laminate according to [7], wherein the barrier substrate further comprises a coating layer on the surface of the inorganic oxide layer opposite to the surface facing the stretched substrate. [9] The laminate according to [7] or [8], wherein the first substrate is the stretched substrate, the second substrate is the barrier substrate comprising the stretched substrate and the inorganic oxide layer, and the second substrate is arranged such that the inorganic oxide layer faces the first adhesive layer and the stretched substrate faces the second adhesive layer.

[10] The laminate according to [7] or [8], wherein the first substrate is a barrier substrate comprising the stretched substrate and the inorganic oxide layer, the first substrate is arranged so that the inorganic oxide layer faces the first adhesive layer and the stretched substrate faces outward, and the second substrate is the stretched substrate.

[11] The laminate according to any one of [1] to

[10] above, wherein the content of polypropylene in the total amount of resin materials contained in the laminate is 80 mass % or more.

[12] The laminate according to any one of the above [1] to

[11] , which is a packaging material.

[13] A packaging bag comprising the laminate according to any one of [1] to

[12] above.

[14] The packaging bag according to

[13] above, which is a pouch for containing retort food or boiled food. EXAMPLES

[0165] The laminate and packaging bag of the present disclosure will be specifically described below based on specific examples.

[0166] [Preparation of transparent barrier substrate] A hydroxyl-containing acrylic resin (number average molecular weight: 25,000, glass transition temperature: 99°C, hydroxyl value: 80mgKOH / g) was diluted with a mixed solvent of methyl ethyl ketone and ethyl acetate (mixing ratio 1:1) until the solid content concentration was 10% by mass to prepare a base material. An ethyl acetate solution containing tolylene diisocyanate (solid content 75% by mass) was added to the base material as a curing agent to obtain a solution for forming a surface coating layer. The amount of the curing agent used was 10 parts by mass relative to 100 parts by mass of the base material.

[0167] A biaxially stretched polypropylene film (ME-1, manufactured by Mitsui Chemicals Tohcello Co., Ltd.) having a thickness of 20 μm and having one side subjected to corona treatment was prepared. The above-mentioned solution for forming a surface coating layer was applied to the corona-treated surface of the film and dried to form a surface coating layer having a thickness of 0.5 μm. In this manner, a resin substrate was obtained.

[0168] A carbon-containing silicon oxide (silica) vapor deposition film with a thickness of 12 nm was formed on the surface coating layer of the resin substrate by a roll-to-roll method using a low-temperature plasma chemical vapor deposition apparatus while applying tension to the resin substrate (CVD method). The vapor deposition film formation conditions were as follows:

[0169] (Formation conditions) Hexamethyldisiloxane:oxygen gas:helium=1:10:10 (unit: slm) Cooling / electrode drum power supply: 22kW Line speed: 100m / min

[0170] The carbon percentage C, silicon percentage Si, and oxygen percentage O in the carbon-containing silicon oxide vapor deposition film were measured. The carbon percentage C, silicon percentage Si, and oxygen percentage O were 32.7%, 29.8%, and 37.5%, respectively, based on 100% of the total of the three elements silicon, oxygen, and carbon. The percentages of each element were measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the measurement conditions described above.

[0171] 385g of water, 67g of isopropyl alcohol, and 9.1g of 0.5N hydrochloric acid were mixed to obtain a solution with a pH of 2.2. 175g of tetraethoxysilane as a metal alkoxide and 9.2g of glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed with this solution while cooling to 10°C to obtain solution A. 14.7g of polyvinyl alcohol with a saponification value of 99% or more and a polymerization degree of 2400 as a water-soluble polymer, 324g of water, and 17g of isopropyl alcohol were mixed to obtain solution B. Solution A and solution B were mixed at a mass ratio (solution A:solution B) of 6.5:3.5 to obtain a barrier coating agent. The barrier coating agent was coated on the deposition film formed on the resin substrate by spin coating, and the mixture was heated in an oven at 80°C for 60 seconds to form a barrier coating layer with a thickness of 300 nm.

[0172] In this manner, a transparent barrier substrate was obtained comprising, in this order, a 20 μm-thick biaxially oriented polypropylene film, a 0.5 μm-thick surface coating layer, a 12 nm-thick carbon-containing silicon oxide (silica) vapor deposition film, and a 300 nm-thick barrier coating layer.

[0173] [glue] The following two-component curing adhesive was used, which is composed of a base agent and a curing agent. Adhesive A Base: Polyester polymer (Mw: 3,500) Hardener: Mixture of IPDI and HDI (higher HDI content than IPDI) Molar ratio of base agent to hardener (NCO / OH): 2 Adhesive A is substantially free of solvent. Adhesive B Base: Polyester polymer (Mw: 4,000) Hardener: Mixture of HDI and XDI Molar ratio of base agent to hardener (NCO / OH): 2 Adhesive B is substantially free of solvent. Adhesive C Base: Polyester polyurethane polymer (Mw: 30,000) Hardener: A mixture of isophorone diisocyanate (IPDI) trimer and xylylene diisocyanate (XDI) trimethylolpropane (TMP) adduct. Molar ratio of base agent to hardener (NCO / OH): 4 Adhesive C contains ethyl acetate as a solvent.

[0174] [Example 1] As a first substrate, a biaxially stretched polypropylene film (P2171, manufactured by Toyobo Co., Ltd., hereinafter also referred to as "BOPP film") having a thickness of 20 μm and one surface of which was corona-treated was prepared. As a second substrate, the above transparent barrier substrate was prepared. As a sealant layer, a 60 μm-thick unstretched polypropylene film (ET-20, manufactured by Okamoto Corporation, hereinafter also referred to as "CPP film") one side of which had been corona-treated was prepared.

[0175] A printed layer having a coating thickness of 1 μm (when dried) was formed on the corona-treated surface of the BOPP film as the first substrate by the gravure roll coating method. Adhesive A was applied onto the printed layer by the gravure roll coating method, and the adhesive layer surface formed on the first substrate and the barrier coat layer surface of the transparent barrier substrate were bonded together, and aged at 40° C. for 72 hours. The thickness of the formed first adhesive layer was 1.35 μm. Furthermore, a corona treatment was performed on the non-barrier coat layer surface of the transparent barrier substrate, and adhesive C was applied by the gravure roll coating method, and the adhesive layer surface formed on the transparent barrier substrate and the corona-treated surface of the CPP film were bonded together, and aged at 40° C. for 72 hours. The thickness of the formed second adhesive layer was 3.15 μm.

[0176] In this manner, the laminate of Example 1 was obtained. The obtained laminate had a layer structure of BOPP film (20 μm) / printed layer (1 μm) / adhesive layer (1.35 μm) / transparent barrier substrate (21 μm) / adhesive layer (3.15 μm) / CPP film (60 μm). The numbers in parentheses indicate the thickness of each layer.

[0177] [Examples 2 and 3] The laminates of Examples 2 and 3 were prepared in the same manner as Example 1, except that the adhesive type and / or thickness of the second adhesive layer was changed as described in Table 1.

[0178] [Example 4] As in Example 1, a biaxially oriented polypropylene film (manufactured by Toyobo Co., Ltd., P2171, BOPP film) having a thickness of 20 μm and having one surface subjected to a corona treatment was prepared as a first substrate. As a second substrate, a biaxially oriented polypropylene film (P2271, BOPP film, manufactured by Toyobo Co., Ltd.) having a thickness of 20 μm and having been corona-treated on both sides was prepared. As in Example 1, a 60 μm-thick unstretched polypropylene film (manufactured by Okamoto Corp., ET-20, CPP film) one side of which had been corona-treated was prepared as a sealant layer.

[0179] A printed layer having a coating thickness of 1 μm (when dried) was formed on the corona-treated surface of the BOPP film as the first substrate by the gravure roll coating method. Adhesive A was applied onto the printed layer by the gravure roll coating method, and the adhesive layer surface formed on the first substrate and one side of the BOPP film as the second substrate were bonded together, and aged at 40° C. for 72 hours. The thickness of the formed first adhesive layer was 1.35 μm. Furthermore, adhesive C was applied to the other side of the BOPP film as the second substrate by the gravure roll coating method, and the adhesive layer surface formed on the BOPP film as the second substrate and the corona-treated surface of the CPP film were bonded together, and aged at 40° C. for 72 hours. The thickness of the formed second adhesive layer was 3.15 μm.

[0180] In this manner, a laminate of Example 4 was obtained. The obtained laminate had a layer structure of BOPP film (20 μm) / printed layer (1 μm) / adhesive layer (1.35 μm) / BOPP film (20 μm) / adhesive layer (3.15 μm) / CPP film (60 μm). The numbers in parentheses indicate the thickness of each layer.

[0181] [Comparative Example 1] A laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that the type of adhesive and / or the thickness of the first adhesive layer was changed as shown in Table 1.

[0182] The laminates of Examples 1 to 4 and Comparative Example 1 described so far all have a printed layer, but instead of the laminates of Examples 1 to 4 and Comparative Example 1, a laminate not having a printed layer may also be used.

[0183] The laminates of Examples 1 to 4 and Comparative Example 1 were subjected to retort sterilization under retort conditions of 121° C., 30 minutes, and 0.21 MPa. Using the laminates after retort sterilization, the following elastic modulus of the adhesive layer, the composite elastic modulus of the sealant layer, and the tear properties were evaluated.

[0184] [Measurement of elastic modulus of adhesive layer] For the laminate after retort sterilization, a force curve was measured using an atomic force microscope (AFM), and the elastic modulus of the cross section of the adhesive layer was calculated from the obtained force curve. The specific measurement procedure is as follows. The laminate after retort sterilization was embedded in an embedding resin to prepare a block, and the block was cut using a commercially available rotary microtome at room temperature (25°C) to prepare a cross section of the laminate. The cross section was obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing was performed with a diamond knife. Using an atomic force microscope (AFM), mapping measurements were performed on the above cross section at a 2.5 μm square including the cross section of the adhesive layer. For the cross section of the adhesive layer, 20 force curves that provided an appropriate force curve shape were selected. Each force curve was fitted according to the JKR (Johnson-Kendall-Roberts) theory to calculate the elastic modulus, and the arithmetic mean value (hereinafter also referred to as the "first arithmetic mean value") of the obtained 20 elastic moduli was calculated. Here, the selected part of the force curve was the vicinity of the center in the thickness direction of the adhesive layer among the parts where the cross section of the adhesive layer was exposed. Three elastic moduli close to the first arithmetic mean value were selected from the above 20 elastic moduli, and the arithmetic mean value (hereinafter also referred to as the "second arithmetic mean value") of the three elastic moduli was calculated. The obtained second arithmetic mean value was taken as the elastic modulus of the cross section of the adhesive layer.

[0185] The details of the AFM measurement conditions are shown below. (AFM elastic modulus measurement) Device name: SPM-9700HT (Shimadzu Corporation) Measurement atmosphere: At room temperature (25℃) Measurement mode: Contact mode Calibration method: Measure the cantilever sensitivity using glass ·Number of measurement points: 64 x 64 points (4096 points in total) Field of view: 2.5μm square Cantilever type: CONTR (manufactured by Nanoworld) Cantilever tip radius: <8nm Cantilever spring constant: 0.2N / m Contact pressure: 0.5V Scan speed: 3Hz Elastic modulus calculation model: JKR (Johnson-Kendall-Roberts) theory Poisson's ratio of sample: 0.4 Analysis software: Nano 3D Mapping (Shimadzu Corporation)

[0186] [Measurement of the composite elastic modulus of the sealant layer] The composite elastic modulus of the sealant layer (Er ) was measured based on the nanoindentation method using a nanoindenter (Bruker's "TI950 TriboIndenter") with the cross section of the sealant layer as the measurement surface. A Berkovich indenter (triangular pyramid indenter; Berkovich_TI0039) was used as the indenter for the nanoindenter. The indenter was pressed into three locations in the exposed cross section of the sealant layer: a position 2 μm inward from the interface with the adhesive layer in the thickness direction of the sealant layer, near the center, and a position 2 μm inward from the seal surface. The measurement conditions were a load control method (indentation load 30 μN, load 3 s / hold 5 s / unload 3 s). The specific measurement procedure is as follows. The laminate after retort sterilization was embedded in an embedding resin to prepare a block, and the block was cut using a commercially available rotary microtome at room temperature (25°C) to prepare a cross section of the laminate. The cross section was obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing was performed with a diamond knife. The indenter was pressed into the sealant layer from the cross section of the sealant layer to a load of 30 μN over a period of 3 seconds, and the load was held for 5 seconds. The load was then removed over a period of 3 seconds. This resulted in the maximum load P max , contact projection area A at maximum depth p The load-displacement curve was obtained, and the composite elastic modulus was calculated from the load-displacement curve. The measurement was carried out in a room temperature (23°C) environment. Measurements are performed at five or more points on the same cross section, and the composite elastic modulus E r is expressed as the arithmetic mean value of five points measured with good repeatability.

[0187] [Evaluation of tearability] As shown in Fig. 20, the laminate 1 after retort sterilization was cut into a size of 55 mm length (MD direction) × 50 mm width (TD direction), and a linear notch 52 (I notch) with a length of 5 mm was made in the center of the upper left and right ends (positions 25 mm away from the left and right ends) to form a test piece. Two test pieces were prepared. Two test pieces were stacked with the sealant layers facing each other so that the positions of the notches of the test pieces were aligned in a plan view. The two test pieces were torn together by hand in the machine direction (MD) using the notch as the base point. The ease of tearing was evaluated based on the following criteria A to E. A: There was no snagging when tearing started, and after tearing started, it was possible to tear without applying excessive force. B: When tearing began, there was a slight snag between the first substrate and the second substrate on the front side of the test piece, but after tearing began, it could be torn without applying excessive force. C: When tearing began, there was a slight catch between the first substrate and the second substrate on the front side of the test piece, and it gradually became more difficult to tear as the tearing continued. D: When tearing began, there was a slight snag between the first substrate and the second substrate on the front side of the test piece, and after tearing began, there was a snag between the second substrate and the sealant layer on the back side of the test piece, causing the sealant layer to stretch and making it difficult to tear. E: Both at the time of and after the start of tearing, the first substrate / second substrate of the front test piece got caught, and the test piece could not be torn apart without applying excessive force.

[0188] Furthermore, the first substrate, the second substrate and the sealant layer used in the laminates of Examples 1 to 4 and Comparative Example 1 were subjected to retort sterilization under retort conditions of 121° C., 30 minutes and 0.21 MPa. The thermal shrinkage rate in the MD direction of the first base material after retort sterilization was calculated according to the following formula. Heat shrinkage rate (%) in the MD direction of the first substrate after retort sterilization = (length in the MD direction of the first substrate before retort sterilization - length in the MD direction of the first substrate after retort sterilization) / length in the MD direction of the first substrate before retort sterilization × 100 The heat shrinkage rate in the MD direction of the second substrate after retort sterilization and the heat shrinkage rate in the MD direction of the sealant layer after retort sterilization were also calculated in the same manner.

[0189] Furthermore, for the oriented polypropylene substrates constituting the first substrate and the second substrate after the retort sterilization, the mesopentad fraction and ethylene content were measured as described below.

[0190] [Measurement of mesopentad fraction and ethylene content] A stretched polypropylene substrate was dissolved in the following solvent, and the following apparatus and conditions were used: 13 C-NMR spectrum was measured. ( 13 C-NMR spectrum measurement) Equipment: Bruker AVANCE NEO700 Probe: 5mmφ CPDCH Observation core: 13 C(176.1MHz) Solvent: 1,1,2,2-tetrachloroethane-d2 ·Concentration: 60mg / 0.6mL Number of times: 2048 ·Temperature: 130℃ Pulse width: 3.3μsec Observation time: 1.6 seconds Latency: 1.4 seconds Measurement mode: Power-gated decoupling

[0191] For the spectrum derived from methyl groups, each peak was assigned to 5 chains of propylene units (mmmm) at 21.86 ppm, and the area of ​​each peak was calculated. The ratio of the area of ​​the peak at 21.86 ppm to the area of ​​all peaks derived from methyl groups was determined as the mesopentad fraction of the stretched polypropylene substrate. In addition, when the polypropylene constituting the stretched polypropylene substrate is a copolymer of polypropylene and ethylene, a peak derived from the methyl group contained in the propylene unit adjacent to the ethylene unit is observed at the position of 20.9 ppm. When the peak is observed, the ratio of the area of ​​the peak at 20.9 ppm to the area of ​​all peaks derived from the methyl group divided by 2 was used as the ethylene content of the stretched polypropylene substrate. The reason for dividing by 2 is that there are two propylene units adjacent to one ethylene unit. On the other hand, when the peak is not observed, the ethylene content of the stretched polypropylene substrate was set to 0.00 mol%.

[0192] [Table 1] [Explanation of symbols]

[0193] 1: laminate, 10: oriented polypropylene substrate, 20: barrier substrate, 21: polypropylene layer, 22: oriented polypropylene substrate, 23: surface coating layer, 24: inorganic oxide layer, 25: coating layer, 26: surface resin layer, 27: adhesive resin layer, 30: sealant layer, 40A, 40B: adhesive layers, 50: packaging bag, 51: easy-to-open portion, 52: notch portion, 53: half-cut line, 60: standing pouch, 61: body (side sheet), 62: bottom (bottom sheet), 63: steam release mechanism, 63a: steam release seal part, 63b: non-seal part

Claims

1. A first substrate; a first adhesive layer; A second substrate; a second adhesive layer; A sealant layer; A laminate having the following in this order in the thickness direction: The first substrate comprises a stretched substrate containing polypropylene as a main component, The second substrate comprises a stretched substrate containing polypropylene as a main component, The sealant layer contains polypropylene as a main component, A laminate, wherein the elastic modulus of the cross section of the first adhesive layer measured using an atomic force microscope (AFM) is 30.0 MPa or more, and the thickness of the first adhesive layer is 0.5 μm or more and 3.0 μm or less.

2. The laminate of claim 1 , wherein the elastic modulus of the cross section of the second adhesive layer is less than 30.0 MPa as measured using an atomic force microscope (AFM).

3. The laminate of claim 2 , wherein the thickness of the first adhesive layer is greater than the thickness of the second adhesive layer.

4. The laminate according to claim 1 , wherein the elastic modulus of the cross section of the second adhesive layer is 30.0 MPa or more as measured with an atomic force microscope (AFM).

5. The laminate of claim 4 , wherein the second adhesive layer has a thickness less than the thickness of the first adhesive layer.

6. The laminate according to claim 1 , wherein the second adhesive layer has a thickness of 0.5 μm or more and 10.0 μm or less.

7. The laminate according to claim 1 , wherein at least one selected from the first substrate and the second substrate is a barrier substrate further comprising an inorganic oxide layer.

8. The laminate according to claim 7 , wherein the barrier substrate further comprises a coating layer on a surface of the inorganic oxide layer opposite to a surface facing the stretched substrate.

9. the first substrate is the stretched substrate, 8. The laminate according to claim 7, wherein the second substrate is a barrier substrate comprising the stretched substrate and the inorganic oxide layer, and the second substrate is disposed such that the inorganic oxide layer faces the first adhesive layer and the stretched substrate faces the second adhesive layer.

10. the first substrate is a barrier substrate including the stretched substrate and the inorganic oxide layer, and the first substrate is disposed such that the inorganic oxide layer faces the first adhesive layer and the stretched substrate faces outward; The laminate of claim 7 , wherein the second substrate is the stretched substrate.

11. The laminate according to any one of claims 1 to 10, wherein a content ratio of polypropylene to a total amount of resin materials contained in the laminate is 80 mass% or more.

12. The laminate according to any one of claims 1 to 10, which is a packaging material.

13. A packaging bag comprising the laminate according to any one of claims 1 to 10.

14. The packaging bag according to claim 13, which is a pouch for containing retort food or boiled food.

Citation Information

Patent Citations

  • Aliphatic polyester film and packaging material

    JP2005053223A